Systematic investigation of recipient cell genetic requirements reveals important surface receptors for conjugative transfer of IncI2 plasmids - Nancy Allard; Arianne Collette; Josianne Paquette; Sébastien Rodrigue; Jean-Philippe Côté (Communications Biology, 2023)
Abstract Bacterial conjugation is a major horizontal gene transfer mechanism. While the functions encoded by many conjugative plasmids have been intensively studied, the contribution of recipient chromosome-encoded genes remains largely unknown. Here, we analyzed the genetic requirement of recipient cells for conjugation of IncI2 plasmid TP114, which was recently shown to transfer at high rates in the gut microbiota. We performed transfer assays with ~4,000 single-gene deletion mutants of Escherichia coli. When conjugation occurs on a solid medium, we observed that recipient genes impairing transfer rates were not associated with a specific cellular function. Conversely, transfer assays performed in broth were largely dependent on the lipopolysaccharide biosynthesis pathway. We further identified specific structures in lipopolysaccharides used as recipient cell surface receptors by PilV adhesins associated with the type IVb accessory pilus of TP114. Our strategy is applicable to study other mobile genetic elements and understand important host cell factors for their dissemination.